Effect of Reduced Temperature and Cryoprotectants on Germinating Capacity and Sprouting Energy of Soy Beans - Shevchenko, N. O.; Zhmurko, V. V.; Strybul, T. F.; Kobyzeva, L. M. (Problems of Cryobiology and Cryomedicine, 2002)
Authors investigated the effect of soy seeds treatment on a sprouting energy and germinating capacity under low positive temperatures (8Â°Ð¡) with propane diol (PD) cryoprotectants PEO-400 and PEO-1500 . The results testify that after the effect of reduced temperature the springing energy and soy seeds sprouting for Soyer 2-95 variety increased under the effect of 7% PD, and of 7- and 15% PEO-400, and for Podilska-1 variety increased under the effect of 15- and 7% PD, and of 15% PEO-400. In the majority of cases PEO-1500 cryoprotectant manifested an inhibiting effect in both varieties.